ANALYSIS OF THE PROS AND CONS OF LEARNING A FOREIGN LANGUAGE EARLY - Ishankulova, Diyora (Журнал иностранных языков и лингвистики, 2023)
As the global preference for second language learning accelerates, this article illustrates the pros and cons of early second language learning by analyzing relevant research and articles. The benefits of learning a second language are based on the prefrontal cortex in the brain, which can help boost cognitive development such as attention span, memory, and creativity. Learning a second language can benefit cognitive development and academic development. On the other hand, learning a second language too early can lead to the loss of the mother tongue, and insufficient command of the mother tongue makes learning a foreign language more difficult. School stress and external factors such as a lack of education can also complicate the second language process.